Antimicrobial resistance of the microbiota of the ear canal, in patients with normal physiological conditions - Vásquez-Paredes, Oscar Fernando; Moscoso-Piedra, Andrés Leonardo; Maldonado-Cornejo, Manuel Esteban; Castillo Hidalgo, Edy Paúl (Revista Científica de la Facultad de Ciencias Veterinarias, 2023)
Verifying its clinical relevance, one of the organs is considered the most is the ear, since it allows earing and additionally, provides the sense of balance. On research for preliminary outcomes, the increase in microbial resistance has dramatically reduced the chances of effective treatment and substantially increased the risk of mortality in several strains with resistance mechanisms in infectious treatments; all this due to the large-scale use of antibiotics. Through the selective culture method Müeller Hinton, all patients with normal physiological conditions were evaluated to detect apparent antimicrobial resistance in the microbiota of the ear canal, obtaining as a result that out of the total number of canine individuals under study, 28.5% presented resistance, at least one antibacterial drug, being considered an alarming affair that generates a risk to the health of animals.